Financial Risk Management in International Business - Ashurakhunov , Abdufattokh (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This research paper explores the major financial and political risks encountered by organizations engaged in international business activities, emphasizing the importance of effective risk management in a globalized economy. In today’s interchained financial landscape, companies seeking to expand across borders face heightened exposure to uncertainties such as foreign exchange volatility, political instability, and fluctuating regulatory environments. These risks can disrupt operations, reduce profitability, and threaten long-term financial stability. The study analyzes the key categories of financial risks—particularly foreign exchange and political risks—and evaluates the strategies companies can adopt to mitigate their impact. Special attention is given to hedging techniques, diversification, and governance frameworks that enhance resilience in international financial markets. The objective of this research is not merely to identify potential risks but to examine the practical mechanisms for managing and minimizing them efficiently. The findings aim to provide a comprehensive understanding of how effective financial risk management contributes to sustainable growth and competitive advantage in international business.